Gerunds in Mongolian and Turkic languages - Rassadin, Valentin I. (The New Research of Tuva, 2012)
Article sets up the system of gerunds in Mongolian and Turkic languages. Comparison shows different principles in organizing of those system and reveals their typological generality with minimal material similarity.
Keywords: gerund system; gerunds organization principles; Mongolian languages; Turkic languages